Yiddish Translation in Canada: A Litmus Test for Continuity - Margolis, Rebecca (TTR)

(untitled) (Association canadienne de traductologie, 2006)
AbstractYiddish translation has been a two-way phenomenon in Canada in the twentieth century that mirrors the changing identity of Jews of Eastern European origin. The Yiddish press translated Canada to the Jewish immigrant masses while Yiddish schools translated ideology to their children. Translations from world literature into Yiddish that appeared in a series of literary journals in the 1920s and 1930s introduced art and ideas to their readerships and demonstrate that Yiddish is a language on a par with other modern languages. Translations from sacred Hebrew-Aramaic texts served both to bring these texts to readers in their vernacular, and, in particular in the post-Holocaust era, as monuments to a lost tradition. Conversely, translations from Yiddish into English allowed authors a wider readership as Jews began to acculturate and adopt English as their primary language. Most recently, Yiddish translations into both French and English have created wider access to both literature and non-fiction materials among non-Yiddish readers.